Find the area of the triangle with the given measurements. Round the solution to the nearest hundredth if necessary.
1 answer:
![\bf \textit{Law of Cosines}\\ \quad \\ c^2 = {{ a}}^2+{{ b}}^2-(2{{ a}}{{ b}})cos(C)\implies c = \sqrt{{{ a}}^2+{{ b}}^2-(2{{ a}}{{ b}})cos(C)}\\\\ -----------------------------\\\\ b = \sqrt{{{ a}}^2+{{ c}}^2-(2{{ a}}{{ c}})cos(B)} \\\\\\ b=\sqrt{{{ 11}}^2+{{ 18}}^2-2(11\cdot 18)cos(104^o)} \\\\\\ b\approx 23.25512998582180400481\implies b\approx 23.26](https://tex.z-dn.net/?f=%5Cbf%20%5Ctextit%7BLaw%20of%20Cosines%7D%5C%5C%20%5Cquad%20%5C%5C%0Ac%5E2%20%3D%20%7B%7B%20a%7D%7D%5E2%2B%7B%7B%20b%7D%7D%5E2-%282%7B%7B%20a%7D%7D%7B%7B%20b%7D%7D%29cos%28C%29%5Cimplies%20%0Ac%20%3D%20%5Csqrt%7B%7B%7B%20a%7D%7D%5E2%2B%7B%7B%20b%7D%7D%5E2-%282%7B%7B%20a%7D%7D%7B%7B%20b%7D%7D%29cos%28C%29%7D%5C%5C%5C%5C%0A-----------------------------%5C%5C%5C%5C%0Ab%20%3D%20%5Csqrt%7B%7B%7B%20a%7D%7D%5E2%2B%7B%7B%20c%7D%7D%5E2-%282%7B%7B%20a%7D%7D%7B%7B%20c%7D%7D%29cos%28B%29%7D%0A%5C%5C%5C%5C%5C%5C%0Ab%3D%5Csqrt%7B%7B%7B%2011%7D%7D%5E2%2B%7B%7B%2018%7D%7D%5E2-2%2811%5Ccdot%2018%29cos%28104%5Eo%29%7D%0A%5C%5C%5C%5C%5C%5C%0Ab%5Capprox%2023.25512998582180400481%5Cimplies%20b%5Capprox%2023.26)
so, "b" rounded up is 23.26, now, we know a = 11 and c = 18
well, to get the area then, let us use Heron's formula
You might be interested in
Why yes it is, good question
Answer:
complete your question
Answer:
<h3>-700</h3>
Step-by-step explanation:
![\frac{2.8}{-0.004}\\\\\mathrm{Apply\:the\:fraction\:rule}:\quad \frac{a}{-b}=-\frac{a}{b}\\\\=-\frac{2.8}{0.004}\\\\\mathrm{Divide\:the\:numbers:}\:\frac{2.8}{0.004}=700\\\\=-700](https://tex.z-dn.net/?f=%5Cfrac%7B2.8%7D%7B-0.004%7D%5C%5C%5C%5C%5Cmathrm%7BApply%5C%3Athe%5C%3Afraction%5C%3Arule%7D%3A%5Cquad%20%5Cfrac%7Ba%7D%7B-b%7D%3D-%5Cfrac%7Ba%7D%7Bb%7D%5C%5C%5C%5C%3D-%5Cfrac%7B2.8%7D%7B0.004%7D%5C%5C%5C%5C%5Cmathrm%7BDivide%5C%3Athe%5C%3Anumbers%3A%7D%5C%3A%5Cfrac%7B2.8%7D%7B0.004%7D%3D700%5C%5C%5C%5C%3D-700)
Answer:
7x - 5 = 11
Step-by-step explanation:
To solve for x, substitute y = -5 into the equation 7x + y = 11.
This becomes 7x + (-5) = 11 or 7x - 5 = 11.